Research on advanced grouting curtain technology for water interception and control at the source of aquifer in coal seam roof - Liu Zhaoxing; Dong Shuning; Zheng Shitian; Shi Zhiyuan (Scientific Reports)
Abstract To solve the problem of safe mining of coal resources affected by the roof breccia aquifer, the author analyzed the scientific location, drilling technology, selection of grouting materials and applicability ratio, grouting pressure and other issues of underground grouting cutoff curtain wall construction, and analyzed and evaluated the grouting effect using water discharge test, drilling coring, drilling cuttings judgment and so on. The research results indicate that the migration range of slurry in both porous and fractured media increases with grouting time, but the growth rate gradually slows. In pore single fracture media, slurry migration preferentially enters the fracture channel and then diffuses along the direction of the fracture into the porous media; For cracks with small openings, pure cement slurry should be used. For karst-developed holes, fly ash can be added for non-pressure filling and injection. Cement slurry with mix proportions of 0.6, 0.7, 0.8, 0.9, water to solid ratios of 2.0, 1.0, 0.8, 0.6, and corresponding fly ash contents of 20%, 20%, 20%, 20%, and 30% can all meet the construction requirements; The minimum safe thickness for the construction of grouting curtain walls is 7.84 m, and the grouting pressure that meets the diffusion range and construction efficiency of the slurry is 4–6 MPa. After inspection of the inspection holes, the saturated compressive strength of the slurry stone body is 11.2 MPa, the water level difference between the inside and outside of the wall reaches 140m in 7 days, and the interception rate is above 86.51%. The interception effect of the wall is significant, meeting the design goals and requirements.